Fluid-Structure Coupling Effects on the Aerodynamic Performance of Airfoil with a Local Flexible Structure at Low Reynolds Number - Kang, Wei; Xu, Min; Zhang, Jia-Zhong (Journal of Applied Nonlinear Dynamics, 2026)
Foreign Object Debris (FOD) is debris or article alien, which may A fluid structure interaction method for an airfoil with a local flexible structure is presented for flow control of Micro Air Vehicles. An improved ALE-CBS scheme is developed for unsteady viscous flow coupling in combination with the theory of shallow arch with large deformation. After the verification of the presented algorithm, the method is used to study the interaction between flow and airfoil with a local flexible structure with different elastic stiffness. The momentum and energy exchange are investigated to reveal the unsteady coupling effects on aerodynamic performance. The results show that the coupling between fluid and structure enhances the momentum and energy exchange from main flow into the boundary layer. It induces the separation bubble moving downstream, and decreases the negative pressure in the separation zone on the upper surface, which leads to lift enhancement. The utilization of local flexible structure can be considered as an effective flow control technique for enhancement of the aerodynamic performance of Micro Air Vehicles.